Experience in implementing social benefits monetization reform in Russia: Literature review - Irina Sinitsina (Center for Social and Economic Research (CASE), 2009)
The present paper is an integral part of the Preparation of the strategy for social benefits monetization reform in Ukraine” project, co-financed by the 2008 Polish aid programme of the Ministry of Foreign Affairs of the Republic of Poland and carried out by CASE in 2008. The paper was prepared as background material aimed at obtaining a better understanding of the main bottlenecks in reforming a vast in-kind benefits system typical for many countries of the Former Soviet Union (FSU). The paper focuses on the following issues: aims and motives of monetization reforms in Russia; expected outcomes of the reform; description of the implementation process; changes of the roles of various actors and agencies; compensation of housing and communal services (HCS) expenses in the course of HCS and monetization reforms; and the major gains and failures of the reform. The paper concludes with lessons that can be derived from the Russian monetization experience for the planned Ukrainian monetization reform. The paper is based on extensive research on the monetization reform in Russia and literature published by leading Russian independent research centers including the Independent Institute for Social Policy (IISP), the Institute for Urban Economics, the Centre for Economic and Financial studies (CEFIR), and the Institute for the Economy in Transition (IET).
Keywords: H53; H77; I39; 330; in-kind benefits; monetization; housing and communal services benefits; targeted social assistance; social sector reform; Russia; transition; Öffentliche Sozialleistungen; Sachtransfer; Sozialpolitik; Sozialreform; Russland